Identification of Clusterin in Buffalo (Bubalus Bubalis) Semen and its Relation to Semen Quality - Kumari, Manisha; Kumar, Pradeep; Kumar, Dharmendra; Yadav , P S (The Indian Journal of Animal Reproduction, 2024)
The study aimed to identify the clusterin in buffalo seminal plasma and compare the semen quality of high and low  clusterin-positive sperm (CPS) bearing buffalo bulls. Semen was collected with artificial vagina technique from buffalo  bulls. The anti-clusterin antibody recognized one protein band of ~40 kDa in the western blot. Based on the results  of the immunofluorescence assay, bulls were divided into two groups: high CPS and low CPS bulls. The expression of  clusterin on sperm cells was further reflected in terms of their quality. The high CPS bulls showed significantly (P
Keywords: CASA; Sperm; Buffalo